Improvement and quality evaluation of gluten-free cake supplemented with sweet potato flour and carrot powder - Md. Abdul Halim; Sulaiman Ali Alharbi; Abdullah A. Alarfaj; Mansour I. Almansour; Mohammad Javed Ansari; Most. Jebun Nessa; Fahriha Nur A Kabir; Anwara Akter Khatun (Applied Food Research, 2024)
Celiac disease and wheat allergy are immune-responsive small bowel disorders that respond solely to the ingestion of gluten-fortified wheat or wheat flour. As a result, for those who are allergic to wheat flour or gluten, the primary treatment is a gluten-free or wheat-free diet. The goal of this research is to develop a gluten-free cake with sweet potato and carrot powder, as well as to examine the Proximate analysis, mineral content, physical properties, and microbiological qualities determined using standard analytical procedures. To make cakes, instead of wheat flour, a combined formulation of 80 % sweet potato flour and 20 % carrot powder, 60 % sweet potato flour and 40 % carrot powder was incorporated into the cake ingredients. Quality evaluation of sample cakes was performed by physicochemical and storage properties. The proximate analysis of the data revealed that the cakes that were created contained adequate levels of protein, fiber, and carbohydrates with percentages ranging from 8.12 to 8.25 %, 3.19–4.19 %, and 36.03 to 38.25 %, respectively. Additionally, an appreciable amount of potassium, calcium, magnesium, phosphorus, and iron have been found in gluten-free cakes. There was color to the gluten-free cakes; L*, a*, and b* ranged from 42.66 to 43.60, 10.03 to 11.21, and 21.81 to 23.28, respectively. There is an assurance of a good color property because the hue and chroma values varied from 11.74 to 25.83 and from 41.02 to 78.03, respectively. The water activity (aw) value ranged from 0.854 to 0.870, which increased from 0.879 to 0.901 during storage. Furthermore, the microbial analysis revealed that the total viable count of all samples remained within the acceptable range after 8 days of storage. The findings of this study show that carrot powder and sweet potato flour can be used to overcome the limitations of gluten-free cakes and improve their nutritional quality.